Analisis Pengambilan Keputusan Konsumen dalam Pembelian Sayur Online di Kota Pontianak - Ayu Safitri; Maswadi Maswadi; Wanti Fitrianti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Currently, to meet daily needs, it can not only be purchased offline but can also be purchased online, including the acquisition of fresh vegetables. The writer aims to identify factors determining consumer decisions in purchasing vegetables online in Pontianak City. The research occurred in Pontianak City, the provincial capital, from June to July. Respondents amounted to 110 people. The writer used a purposive sampling technique to determine the sampling method for this research. The variables under scrutiny encompass consumer decision-making (Y), cultural factors (X1), social factors (X2), personal factors (X3), and psychological factors (X4). The analytical approach of choice is Structural Equation Modeling (SEM). Before conducting data analysis, the data obtained will be tested by testing the validity and reliability first. Subsequently, a fit assessment will be shown to gauge the stages of congruence or Goodness Of Fit (GOF) between the data and the proposed model. The analysis result explains the factors that positively impact consumer decision-making in buying vegetables online are cultural and psychological factors. This is due to the perceptions and attitudes of consumers who are open to new existing cultures so that consumers prefer and want to try the current culture. Psychological factors lead to consumer perceptions and beliefs about buying vegetables online, which creates the desire and encouragement to try buying vegetables online. The better the consumer's perception, the more confident it is for customers to try to repurchase vegetable products online. Consumer knowledge about online shopping is also impactable in making purchasing decisions, and it is because the higher the consumer's knowledge about online shopping, the higher the decision to buy vegetables online.